Freedom is a Point of Departure, Not a Horizon: Review of Gilles Grelet’s Theory of the Solitary Sailor - Smith, Jeremy (Identities: Journal for Politics, Gender and Culture, 2022)
The following is a review of the recently published translation of Theory of the Solitary Sailor by Gilles Grelet (trans. Amy Ireland and Robin Mackaye, Falmouth: Urbanomic, 2022). It highlights the significance of the work, its major stakes, and asks questions regarding the future of Grelet’s methodical anti-philosophical invention. Author(s): Jeremy R. Smith Title (English): Freedom is a Point of Departure, Not a Horizon Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 176-180 Page Count: 4 Citation (English): Jeremy R. Smith, "Freedom is a Point of Departure, Not a Horizon,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 176-80. Author Biography Jeremy R. Smith, Western University Jeremy R. Smith is a PhD Candidate at the Centre for the Study of Theory and Criticism at Western University. He is a co-founder and co-editor of Oraxiom: A Journal of Non-Philosophy.